Influence of pig farming on human Gut Microbiota: role of airborne microbial communities. (1st January 2021) - Moor, Julia; Wüthrich, Tsering; Aebi, Suzanne; Mostacci, Nadezda; Overesch, Gudrun; Oppliger, Anne; Hilty, Markus
ABSTRACT: It has been hypothesized that both genetics and diet influence the composition of the human cecal microbiota. However, it remains unclear whether and how occupational exposure to microbes impacts the microbial communities in human guts. Using a One Health approach, we visited pig farms (n = 26) and collected stool specimens from pig workers (n = 59), pig barn air samples (n = 19), and rectal swabs from pigs at three different growth stages (n = 144). Stool samples from cattle workers were included as a control group (n = 22). Each sample's microbiota was characterized using 16S rRNA gene sequencing and the DADA2 pipeline. We obtained a significantly different clustering of the microbial compositions of pig and cattle workers by permutational multivariate analysis of variance (PERMANOVA; P < .001). Workers primarily exposed to pigs had higher relative abundances of Prevotellaceae and less Bacteroidaceae than workers exposed to cattle. We also found that the microbial compositions of pig workers' stool samples shared extensive fractions with the samples from their pigs. We also identified amplicon sequencing variants (ASVs) in the airborne microbiota which were likely involved in zoonotic transmission events. We hypothesize that ASVs originating from pig feces are aerosolized and, through breathing, get trapped in the pig farm workers' upper respiratory tract from where they can get swallowed. Consequently, some of the animal associated ASVs are transferred into the gastrointestinal tracts (GITs) which leads to changes in the composition of the human gut microbiota. The importance of this finding for human health must be investigated further.